Alterations in the immunoexpression of claudin-1 between different grades of oral epithelial dysplasias - Carvalho, Marianne de Vasconcelos (2017)
Claudins are transmembrane proteins that play a role in cell proliferation and adhesion and tumourigenesis. This study evaluated the immunoexpression of claudin-1 in the oral epithelial dysplasia (OED) (19 mild, 26 moderate, 3 severe). Diffuse staining predominated in mild (89.4%) and moderate (80.8%) OEDs. Immunoexpression in the middle and upper third was observed in all mild cases, whereas in moderate/severe dysplasias staining was observed in the upper third in 41.4% of cases, in the upper and middle third in 41.4%, and in the upper, middle and lower third in 17.2% (P<0.05). All mild OEDs and 73.1% of moderate cases presented only membrane staining, whereas membrane/cytoplasmic staining was observed in severe cases. Staining intensity was weak in 60% of parakeratinized OEDs and moderate/strong in orthokeratinized OEDs (60.8%) (P>0.05). The differences in the immunoexpression of claudin-1 between different grades of OEDs suggest the involvement of this protein in the progression of dysplasias.